Cochlear implantation outcomes in adults: A scoping review. - Isabelle Boisvert; Mariana Reis; Agnes Au; Robert Cowan; Richard C Dowell (PLoS ONE)
Objectives This study aimed to provide a descriptive analysis of recent evidence available in the literature in relation to the efficacy of unilateral cochlear implantation in adults, the general findings of these studies, and the populations to which these findings apply. It also aimed to appraise the individual success rate and the magnitude of benefit following implantation. Design A scoping review was conducted to identify English-language, peer-reviewed journal articles published between 2000 and 2018 assessing the outcomes of cochlear implantation in adults who received their first cochlear implant from 2000 onwards. To be included, studies had to report speech perception or self-reported measures of listening or quality of life at least three months after implantation. Systematic searches were conducted in Medline, Embase, Web of Science and Google Scholar. A two-stage screening approach was used, with seven reviewers independently screening titles and abstracts against inclusion criteria and three from this group further reviewing full-texts. A data charting form was developed and trialled, with 10% of the study data extracted in duplicate to compare results and further refine the form. Data relevant for efficacy analyses were extracted from studies with sample sizes of at least 10 participants. Results A total of 4182 abstracts were screened against inclusion criteria, and of these, 603 full-texts were further screened. After exclusion of non-eligible articles, 201 articles were included in the first part of this scoping review. The majority of these articles were case series or comparative studies without a concurrent group, and had small sample sizes. Data synthesis conducted with the 102 articles with more than 10 participants highlighted that the average word perception ability improved from 8.2% to 53.9% after implantation. Self-reported benefit improved by 21.5 percentage points. At the individual level, 82.0% of adults with postlingual hearing loss and 53.4% of adults with prelingual hearing loss improved their speech perception ability by 15 percentage points or more. A small proportion had poorer ability after implantation or had stopped using the cochlear implant. Conclusions Despite broad inconsistencies in measurement, research design, and reporting across articles, it is evident that cochlear implantation is beneficial to the majority of adults of any age who have limited aided speech perception abilities. While many adults with severe-to-profound hearing loss may also have poor speech perception abilities with hearing aids, the validity of using hearing loss severity as a criterion for cochlear implantation has not been demonstrated. Clinical and research recommendations derived from this review are provided.